A method for accurate spatial registration of PET images and histopathology slices - Puri, T; Chalkidou, A; Roy, A; Henley-Smith, R; Barber, P; Oakley, R; Simo, R; Jeannon, J; McGurk, M; Marsden, P (McDonnell Mackie Publishing, 2016)
Positron emission tomography (PET) is an imaging technique used for the assessment of tissue of interest via administration of radiopharmaceutical commonly known as tracer. A newly developed tracer for PET imaging should be validated by comparison with the gold standard of histopathology imaging before it can add value for clinical purposes, for example, diagnosis, prognosis and response to treatment. The tracer validation studies may become more meaningful if the quantitative comparison between the two PET and histopathology images comes from spatially corresponding regions.